Financial Planning and Financial Instruments: 2013 in Review, 2014 in Prospect - Mark Brimble; Ciorstan Smark (Australasian Accounting, Business and Finance Journal, 2013)
The Global Financial Crisis (GFC); changes in regulation; issues in public perception and trust have contributed to a troubled 2013 for financial planners. As financial planning and wealth management providers seek to bolster their professional status, the Financial Planning Education Council’s National Curriculum and Accreditation Framework and ASIC’s minimum training requirements are also a space to watch. In prospect, 2014 will offer opportunities and challenges in the form of a changed government; regulatory changes; accreditation challenges and the hope of the recruitment of strong financial planning and wealth management professionals for the future.
Keywords: Financial planning; Wealth management; Regulation; National Curriculum; Accreditation Framework